2015
DOI: 10.1007/978-94-017-7342-3_55
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mineral Fillers and Their Fractional Voids on Mastic Rheological and Mechanical Properties

Abstract: Mineral fillers are added into asphalt mixtures to stiffen asphalt binder and improve mixture density and strength. The stiffness of the mastic affects the ability of the mixture to resist permanent deformation at higher temperatures, influences stress development and fatigue resistance at intermediate temperatures, and influences stress development and fracture resistance at low temperatures. In this study, the effect of mineral fillers and their fractional voids on mastic rheological and mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For the modified asphalt mastic, viscosity significantly increases with increasing filler content, but the increase is not significant for neat asphalt mastic [19]. The filler volume fraction is also determined for the mastic depending on the asphalt binder used [20]. In addition, the mastic exhibits both linear and nonlinear viscoelastic behavior like that of the asphalt binder.…”
Section: Introductionmentioning
confidence: 99%
“…For the modified asphalt mastic, viscosity significantly increases with increasing filler content, but the increase is not significant for neat asphalt mastic [19]. The filler volume fraction is also determined for the mastic depending on the asphalt binder used [20]. In addition, the mastic exhibits both linear and nonlinear viscoelastic behavior like that of the asphalt binder.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this approach emerged as the sole independent parameter capable of effectively distinguishing suitable fillers from unsuitable ones. Furthermore, Romeo et al (2016) validated the utility of Rigden Void as an indicator of asphalt hardening filler [4]. Their study highlighted those fillers with larger Rigden Void values exhibited an enhanced capacity for absorbing and dispersing independent asphalt, consequently improving the frictional characteristics of the filler particles, as documented by Zhang et al (2019) [5].…”
Section: Introductionmentioning
confidence: 67%
“…Contemporary asphalt research increasingly incorporates waste natural materials, such as coconut peat and bagasse. Notably, some researchers have found that substituting asphalt with bagasse ash can enhance the stability of Hot Mix Asphalt (HMA) in Marshall specimens [4,5,42]. Recently, bagasse and coconut peat fillers were employed to assess workability and measure pull-off tensile strength [43].…”
Section: Introductionmentioning
confidence: 99%